2015
DOI: 10.1016/j.pbb.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of social contact and drug self-administration

Abstract: Social learning theories of drug abuse propose that individuals imitate drug use behaviors modeled by social peers, and that these behaviors are selectively reinforced and/or punished depending on group norms. Historically, animal models of social influence have focused on distal factors (i.e., those factors outside the drug-taking context) in drug self-administration studies. Recently, several investigators have developed novel models, or significantly modified existing models, to examine the role of proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 77 publications
(99 reference statements)
0
14
0
Order By: Relevance
“…The vast majority of rodent studies examining social behavior have done so in young rodents, during early developmental periods in which social behavior often manifests as rough-and-tumble play (Panksepp et al, 1984; Bredewold et al, 2014; van Kerkhof et al, 2013; Kummer et al, 2011; Pellis et al, 1997; Smith, 2012; Strickland and Smith, 2015; Trezza et al, 2011; Vanderschuren and Trezza, 2014; Veenema et al, 2012; Yates et al, 2013; Zakharova et al, 2009; Zernig and Pinheiro, 2015). Indeed, social processes in young rodents are richly expressed at high levels and lend themselves toward ready delineation of neural substrates underlying social play behavior.…”
Section: 0 Resultsmentioning
confidence: 99%
“…The vast majority of rodent studies examining social behavior have done so in young rodents, during early developmental periods in which social behavior often manifests as rough-and-tumble play (Panksepp et al, 1984; Bredewold et al, 2014; van Kerkhof et al, 2013; Kummer et al, 2011; Pellis et al, 1997; Smith, 2012; Strickland and Smith, 2015; Trezza et al, 2011; Vanderschuren and Trezza, 2014; Veenema et al, 2012; Yates et al, 2013; Zakharova et al, 2009; Zernig and Pinheiro, 2015). Indeed, social processes in young rodents are richly expressed at high levels and lend themselves toward ready delineation of neural substrates underlying social play behavior.…”
Section: 0 Resultsmentioning
confidence: 99%
“…Recently, preclinical studies have begun examining the influence of social peers on drug self-administration and other measures of drug-seeking behavior (see reviews by Neisewander et al, 2012; Bardo et al, 2013; Zernig et al, 2013; Strickland and Smith, 2014, 2015). We recently reported that cocaine intake is facilitated in the presence of a social partner that is also self-administering cocaine, but cocaine intake is inhibited if a social partner is abstinent (i.e., if the partner does not have access to cocaine).…”
Section: The Effects Of Social Cues On Cocaine-seeking Behaviormentioning
confidence: 99%
“…Changes in drug-maintained responding as a function of estrous cycle may be of particular interest when placed in the context of the growing body of literature indicating that drug taking can be influenced by a social partner (for reviews see Strickland and Smith 2014; 2015). Until recently, studies examining the effects of social contact on measures of drug self-administration were limited by the lack of commercially available equipment allowing more than one animal to engage in drug self-administration in close proximity to a partner.…”
Section: Introductionmentioning
confidence: 99%